2016
DOI: 10.1371/journal.pone.0160162
|View full text |Cite
|
Sign up to set email alerts
|

Correction: AarF Domain Containing Kinase 3 (ADCK3) Mutant Cells Display Signs of Oxidative Stress, Defects in Mitochondrial Homeostasis and Lysosomal Accumulation

Abstract: The following reference was incorrectly omitted: Stefely JA, Reidenbach AG, Ulbrich A, Oruganty K, Floyd BJ, et al. (2015)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Our data in rats show an increase in Coq2 , Coq4 , Coq7 and Coq9 expression in the liver after birth ( Figure 5 a) and that of Coq3 , Coq5–7 , Coq9 and Ndufa9 in skeletal muscle ( Figure 5 b). Cullen et al showed that COQ8A interacts with COQ3 , COQ5 , COQ7 and COQ9 in HeLa cells [ 57 , 58 ]. This correlates with another study, which identified PTC7, which was not annotated on the microarray in our study, to be a regulator of CoQ in human HeLa and SH-SY5Y cells [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our data in rats show an increase in Coq2 , Coq4 , Coq7 and Coq9 expression in the liver after birth ( Figure 5 a) and that of Coq3 , Coq5–7 , Coq9 and Ndufa9 in skeletal muscle ( Figure 5 b). Cullen et al showed that COQ8A interacts with COQ3 , COQ5 , COQ7 and COQ9 in HeLa cells [ 57 , 58 ]. This correlates with another study, which identified PTC7, which was not annotated on the microarray in our study, to be a regulator of CoQ in human HeLa and SH-SY5Y cells [ 59 ].…”
Section: Discussionmentioning
confidence: 99%